2004
DOI: 10.1111/j.0001-5172.2004.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐frequency balanced spectral entropy as a measure of anesthetic drug effect in central nervous system during sevoflurane, propofol, and thiopental anesthesia

Abstract: All indices, RE, SE, and BIS, distinguished excellently between conscious and unconscious states during propofol, sevoflurane, and thiopental anesthesia. During burst suppression, Entropy parameters RE and SE, but not BIS, behave monotonously. During regaining of consciousness after a thiopental or propofol bolus, RE and SE values recovered significantly closer to their baseline values than did BIS. Response entropy indicates emergence from anesthesia earlier than SE or BIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(180 citation statements)
references
References 22 publications
9
166
1
4
Order By: Relevance
“…Hence, reliable and more robust electroencephalographic devices are needed to secure continuous cerebral monitoring. One such method may be the spectral entropy of EEG realized in the M-entropy module (GE Healthcare, Brussels, Belgium) that was introduced in 2004 [7]. With this device, the digitized raw EEG signal is first transformed into the frequency domain by fast Fourier transformation to identify sinusoidal components and calculate its power spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, reliable and more robust electroencephalographic devices are needed to secure continuous cerebral monitoring. One such method may be the spectral entropy of EEG realized in the M-entropy module (GE Healthcare, Brussels, Belgium) that was introduced in 2004 [7]. With this device, the digitized raw EEG signal is first transformed into the frequency domain by fast Fourier transformation to identify sinusoidal components and calculate its power spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity and specificity of the entropy were demonstrated in previous reports which showed that entropy is as efficient as Bispectral index in predicting changes in the hypnotic component of anaesthesia, and the changes in SE and RE values followed a similar pattern to the Bispectral index values during propofol induction in adults . (13,14) Also, Anderson and Jakobsson demonstrated good correlation between propofol sedation and entropy indices in young and elderly patients (15). Valjus and colleagues showed low entropy recording during the first 5 min of the anaesthesia .…”
Section: Discussionmentioning
confidence: 98%
“…Approximate entropy can quantify the irregularity of data time series, i.e., the predictability of subsequent amplitude values based upon the knowledge of the previous amplitude values. Entropy of the EEG measures the regularity of the signal: high levels of entropy during anesthesia demonstrate that the subject is awake, whereas low levels of entropy correlate with deeper unconsciousness (Anderson et al , 2004, Bruhn et al , 2003, Hans et al , 2005, Vakkuri et al , 2004.…”
Section: Approximate Entropy (Apen)mentioning
confidence: 99%
“…Researchers have demonstrated that LZC and ApEn can distinguish between awake and anaesthetized state of human subjects (Anderson, Barr, 2004, Bruhn, Bouillon, 2003, Ferenets et al , 2006, Ferenets et al , 2007, Hans, Dewandre, 2005, Kumar et al , 2007, Noh et al , 2006, Vakkuri, Yli-Hankala, 2004, Voss et al , 2006, Zhang, Roy, 2001). In sleep research ApEn was statistically significantly lower during Stage IV and higher during wake and REM sleep (Burioka et al , 2005, Papadelis et al , 2007.…”
Section: Clinical Application Of Nda Correlated With Unconsciousnessmentioning
confidence: 99%